Ubiquitous Sensor Networks and Image Processing Based Environmental Monitoring System for Fire Safety. (26th May 2014) - Lee, Changsoo; Jung, Daewon; Lee, Keun-Wang
Abstract : In recent years, since the tall buildings are getting increased and getting dense in the city area, those buildings can be more and more exposed to risks such as fire and natural disasters. In case if the high-rise building is on fire, it is not easy to put out the fire even with the modernization of the firefighting equipment. These risks can directly lead to human casualties so that it is necessary to quickly have an initial evacuation or initial suppression risks. In this paper, we propose the integrated method for reducing the fire risks through sensors such as temperature and humidity, ZigBee technology, camera control and image processing technologies, and real-time data transmission technology. Based on our proposed method, it is expected that our integrated system directly leads to the expansion of risk safety management system as well as the development of USN technologies.